2004
DOI: 10.4314/ajtcam.v1i1.31093
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of <i>Harpagophytum procumbens</i> dc [Pedaliaceae] secondary root aqueous extract in some mammalian experimental animal models

Abstract: In an attempt to scientifically appraise the 'healing powers' and medicinal value of Harpagophytum procumbens DC root aqueous extract (HPE), and throw some light on the efficacy and safety of the medicinal plant product, the cardiovascular effects of the herb's root aqueous extract (HPE) have been investigated in some mammalian experimental animal models. The results of this laboratory animal study indicate that relatively low to moderate doses of H. procumbens root aqueous extract (HPE, 10-400 mg/kg i. v.) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the experimental model of hyperkinetic ventricular arrhythmias (HVA) using Langendorff preparations of rat heart, Costa De Pasquale et al (1985) observed that H. procumbens methanol extracts and harpagoside produced a dose-dependent, significant, protective effect on HVA-induced reperfusion. Mahomed and Ojewole (2004) found that low to moderate doses of H. procumbens secondary tuber aqueous extract (10-400 mg/kg) produced dose-dependent hypotensive and cardiodepressant effects on the systemic arterial blood pressure and heart rate of pentobarbitone-anaesthetised rats. At doses of 10-1000 mg/ml, dose-dependent, initial slight, transient and significant contractions of isolated rat portal veins, followed by secondary, longer-lasting, significant relaxations of the cardiac muscle were noted.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In the experimental model of hyperkinetic ventricular arrhythmias (HVA) using Langendorff preparations of rat heart, Costa De Pasquale et al (1985) observed that H. procumbens methanol extracts and harpagoside produced a dose-dependent, significant, protective effect on HVA-induced reperfusion. Mahomed and Ojewole (2004) found that low to moderate doses of H. procumbens secondary tuber aqueous extract (10-400 mg/kg) produced dose-dependent hypotensive and cardiodepressant effects on the systemic arterial blood pressure and heart rate of pentobarbitone-anaesthetised rats. At doses of 10-1000 mg/ml, dose-dependent, initial slight, transient and significant contractions of isolated rat portal veins, followed by secondary, longer-lasting, significant relaxations of the cardiac muscle were noted.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Such biphasic activities of plant constituents have been reported previously. [41][42][43][44] However, as explained before, since the secretion of IL-8 was specifically inhibited by certain plant constituents in the post-incubation protocol in a dose dependent manner, the biphasic effect on expression of IL-8 mRNA was not apparent.…”
Section: Discussionmentioning
confidence: 99%
“…To date, scientific studies on some traditional herbs have demonstrated their medicinal value in animal models. 50 Other studies demonstrated anticonvulsant and sedative properties of aqueous extract of Passiflora edulis in laboratory animals. 49 In addition, aqueous extract of H. procumbens was shown to induce dose-related decreases in arterial blood pressure and heart rate in laboratory animal studies.…”
Section: Patients Should Be Protected Regardless Of Who Is Conductinmentioning
confidence: 96%
“…49 In addition, aqueous extract of H. procumbens was shown to induce dose-related decreases in arterial blood pressure and heart rate in laboratory animal studies. 50 Other studies demonstrated anticonvulsant and sedative properties of aqueous extract of Passiflora edulis in laboratory animals. 51 Traditionally, Passiflora herbs have been used to treat health conditions of the nervous system such as epilepsy, insomnia, anxiety and headache.…”
Section: Patients Should Be Protected Regardless Of Who Is Conductinmentioning
confidence: 96%